Combined effects of genetic background and diet on mouse metabolism and gene expression - Jordan N. Reed; Faten Hasan; Abhishek Karkar; Dhanush Banka; Jameson Hinkle; Preeti Shastri; Navya Srivastava; Steven C. Scherping; Sarah E. Newkirk; Heather A. Ferris; Bijoy K. Kundu; Sibylle Kranz; et al. (iScience)
Summary: In humans, dietary patterns impact weight and metabolism differentially across individuals. To uncover genetic determinants for differential dietary effects, we subjected four genetically diverse mouse strains to humanized diets (American, Mediterranean, vegetarian, and vegan) with similar macronutrient composition, and performed body weight, metabolic parameter, and RNA-seq analysis. We observed pronounced diet- and strain-dependent effects on weight, and triglyceride and insulin levels. Differences in fat mass, adipose tissue, and skeletal muscle glucose uptake, and gene expression changes in most tissues were strain-dependent. In visceral adipose tissue, ∼400 genes responded to diet in a strain-dependent manner, many of them in metabolite transport and lipid metabolism pathways and several previously identified to modify diet effects in humans. Thus, genetic background profoundly impacts metabolism, though chosen dietary patterns modify the strong genetic effects. This study paves the way for future mechanistic investigations into strain-diet interactions in mice and translation to precision nutrition in humans.